A comparison of stroke characteristics between team boat (K2) and individual (K1) sprint kayaking - Tay, C. S.; Kong, P. W. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to compare the stroke characteristics of sprint kayakers in team boat (K2) versus individual (K1) 200-m racing. This case study centred on two male 200-m specialists from a national sprint kayak team. High-speed (120 Hz) videos were recorded from the sagittal view during an important selection time trial. Thereafter, video analysis was performed to identify stroke characteristics for each paddler in both K2 and K1, including stroke rate and a four-phase stroke breakdown of entry, pull, exit and aerial sub-phases. Results showed that the kayakers` stroke profile were more similar when comparing between K2 and K1 for the same person, rather than within both paddlers during the K2. It is likely that sprint kayakers have individually preferred stroke profiles but it is not clear how these profiles may be adapted for successful team boat performance.